THE INFLUENCE OF SERVICE QUALITY, PRODUCT AVAILABILITY, PRICE AND LOCATION ON CUSTOMER SATISFACTION AT CESPLENG PHARMACY - Baharuddin, Muhammad Hizba; Wiyadi, Wiyadi (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2024)
In the field of health services, the availability of medicines in complete types and quantities is a target that must be achieved through these factors being taken into consideration when conducting research on the influence of service quality, product availability, price, and location on customer satisfaction, especially at cespleng pharmacies. The research was carried out around the pharmacy business area, which is the community and road users, and obtained a total of 175 respondents who then carried out sample testing using SPSS v.23 using multiple linear regression analysis testing which found that service quality., product availability, price and location had significant value and so good that it can have an influence on customer satisfaction